A profile of occupational tasks performed by mounted police officers. - Canetti, Elisa F.D.; Gersbach-Seib, Ashlee; Moore, Ryan; Schram, Ben; Orr, Robin (Work, 2024)
BACKGROUND: Within individual policing organisations, there are a wide variety of units and job roles. OBJECTIVE: To profile the occupational tasks performed by Australian mounted police officers, aiming to offer conditioning insight into this unique job role. METHODS: Thirteen fully qualified and operational mounted police officers (n = 11 females), who served in the mounted police unit for ∼3.3 (±2.3) years, participated in this observational cohort study. Participants completed a survey outlining common occupational tasks and were monitored throughout four consecutive shifts. Participants' heart rate (HR), respiratory rate (RR), and skin temperature (ST) data were collected via wearable monitoring (Equivital EQ-02, Hidalgo, UK) and body position, physical activity undertaken, task effort, and load carriage were recorded by researchers. A one-way ANOVA was used to assess mean differences in physiological measures between the three most reported tasks. RESULTS: Survey identified 130 tasks, with 38 listed as most common. The three most reported mounted police tasks were: 'horse riding' (n = 13, 34%), 'mounted patrols' (n = 10, 26%), and 'horse care' (n = 10, 26%). These were also reported as the most physically demanding. HR during 'horse care' and 'horse riding' were significantly higher than when 'mounted patrolling' (27±7bpm, p = 0.001 and 33±8bpm; p = 0.001, respectively). Mean RR was higher when 'horse riding' when compared to 'horse care' (5.3±1.6brpm) and 'mounted patrol' (8.5±1.9brpm). CONCLUSION: Mounted police officers experience unique physiological challenges throughout their routine occupational tasks. This study highlights the significance of understanding occupation-specific tasks and stressors undertaken by mounted police to develop relevant conditioning, rehabilitation, and monitoring procedures.